KERUSAKAN TEGAKAN TINGGAL AKIBAT EKSPLOITASI HUTAN DENGAN SISTEM TRAKTOR DAN HIGHLEAD - Jurnalis Thaib (Pusat Penelitian dan Pengembangan Hasil Hutan, 1985)
Tractor and highlead yarding systems are the most common logging systems in the Indonesian Selective Cutting (TPI) of its tropical rain forest exploitations. The study of the logging system performances were conducted to evaluate the extend of residual stand damages. Studies in 22 forestry concessions revealed that the TPI concepts have not been adopted satisfactorily. The study also confirmed that the average number of trees having 35 cm minimum diameter are 11.6-70.8 trees per ha of commercial species and 18. 7-79.4 trees per ha for all species. With regard to the TPI, there were only 52.6 percent of the forest concessions conformed with the specified conditions where at least 25 potential trees per ha should remained in the residual stands.Comparative study with highlead yarding system indicated that average number of potential trees in the residual stands were 5.1-16.6 trees per ha of commercial species and only 6.3-21. 7 trees per ha for all species. None of the concessions with highlead logging systems have met the TPI requirements.The residual stand damage when using highlead yarding are significantly higher (P < .05) in comparison with that of the tractors.The residual stand damages were 68.7 to 71.7 percent for highlead system while only 3.9-52.2 percent for the tractor. The study concluded that with respect to damages, tractor yarding is preferable over highlead.